Personal Political Branding: Strategi Kampanye Ganjar Pranowo Untuk Pilpres 2024 di Social Media Twitter - Sitti Hadjira; Suranto Suranto (Fakultas Ilmu Komunikasi UKWMS, 2023)
In this digital age, social media has become a powerful platform to communicate and influence public opinion. A critical aspect of using social media is its ability to strengthen political branding, which is how a politician or political party builds their image and identity in the eyes of the public. Political branding refers to creating a political image and identity for a candidate, political party, or political movement in society. Ganjar Pranowo, as the Governor of Central Java, utilizes Twitter as a medium to strengthen the value of political branding. This research aims to explain Ganjar Pranowo's political branding strategy through his Twitter social media account. This research uses a qualitative method; then, the researcher uses the Nvivo 12Plus application to analyze the data. The results of this study show that political branding efforts made by Ganjar Pranowo include: First, Ganjar Pranowo presents himself as a religious leader. Second, Ganjar Pranowo presents himself as a leader close to middle to lower-class people. Third, Ganjar Pranowo presents himself as a leader who upholds ethnicity and culture. Fourth, Ganjar Pranowo displays that he is a leader who supports improving the community's economy through UMKM. Fifth, Ganjar Pranowo presents himself as a leader close to the younger generation. Ganjar Pranowo's political branding capability lies in personality attributes. The personal attributes found in the Twitter account @ganjarpranowo include: First, competence as a leader. Second, passion and dedication. Third, leadership style. This research is expected to provide an overview related to political branding from political actors and stakeholders. ABSTRAK Di era digital ini, media sosial telah menjadi platform yang kuat untuk berkomunikasi dan memengaruhi opini publik. Salah satu aspek penting dari penggunaan media sosial adalah kemampuannya dalam memperkuat political branding, yaitu cara seorang politisi atau partai politik membangun citra dan identitas mereka di mata masyarakat. Political branding merujuk pada sebuah proses membangun citra dan identitas politik untuk seorang kandidat, partai politik, atau gerakan politik tertentu di masyarakat. Ganjar Pranowo sebagai Gubernur Jawa Tengah memanfaatkan twitter sebagai media penguatan nilai political branding. Penelitian ini bertujuan untuk memaparkan bagaimana strategi political branding Ganjar Pranowo melalui akun media sosial twitter. Penelitian ini menggunakan metode kualitatif, kemudian dalam melakukan analisis data peneliti menggunakan aplikasi Nvivo 12Plus. Hasil dari penelitian ini menunjukkan bahwa upaya political branding yang dilakukan oleh Ganjar Pranowo meliputi: Pertama, Ganjar Pranowo menampilkan bahwa dirinya seorang pemimpin yang religius. Kedua, Ganjar Pranowo menampilkan bahwa dirinya seorang pemimpin yang memiliki kedekatan dengan masyarakat menengah kebawah. Ketiga, Ganjar Pranowo menampilkan bahwa dirinya seorang pemimpin yang menjunjung tinggi suku dan budaya. Keempat, Ganjar Pranowo menampilkan bahwa dirinya seorang pemimpin yang mendukung peningkatan ekonomi masyarakat melalui UMKM. Kelima, Ganjar Pranowo menampilkan bahwa dirinya seorang pemimpin yang dekat dengan generasi muda. Kapabilitas political branding Ganjar Pranowo terletak pada personality attributes. Atribut personal yang ditemukan dalam akun twitter @ganjarpranowo diantaranya: Pertama, Kompetensi sebagai seorang pemimpin. Kedua, Semangat dan dedikasi. Ketiga, Gaya kepemimpinan. Penelitian ini diharapkan dapat memberikan gambaran terkait political branding dari aktor politik sekaligus pemangku kepentingan.